A wide search of obscured Active Galactic Nuclei using XMM-Newton and WISE. Issue Volume 9:Issue S304(2013) (25th July 2014) - Rovilos, E.; Georgantopoulos, I.; Akylas, A.; Aird, J.; Alexander, D. M.; Comastri, A.; Del Moro, A.; Gandhi, P.; Georgakakis, A.; Harrison, C. M.; Mullaney, J. R.
Abstract: We use the WISE all sky survey observations to look for counterparts of hard X-ray selected sources from the XMM-Newton -SDSS survey. We then measure the 12 μm luminosity of the AGN by decomposing their optical to infrared SEDs with a host and an AGN component and compare it to the X-ray luminosity and their expected intrinsic relation. This way we select 20 X-ray under-luminous heavily obscured candidates and examine their X-ray and optical properties in more detail. We find evidence for a Compton-thick nucleus for six sources, a number lower than what expected from X-ray background synthesis models, which shows the limitations of our method.